THE INFLUENCE OF DIGITALIZATION AND KNOWLEDGE ON PEOPLE’S INTEREST IN PAYING ZAKAT THE PANDEMIC ERA - Sylvia Nuraini; Budiandru Budiandru (Universitas Muhammadiyah Surakarta, 2023)
The covid-19 pandemic has impacted all aspects of life. One of the economic fields affected by the covid-19 pandemic is the zakat institution. Zakat institutions need to innovate in collecting zakat during the covid-19 pandemic. This study aims to collect empirical evidence on the effect of digitization of zakat and zakat knowledge on interest in paying zakat in BAZNAS DKI Jakarta during the pandemic Era. The research method used is quantitative. The sample in this study is the Community District Ciracas. Sampling in this study using purposive sampling techniques and data analysis techniques used are multiple linear regression analysis using Eviews program Version 9 and Microsoft excel 2013. The results of this study indicate that the variables of digitization of zakat and knowledge of zakat simultaneously affect the variables of interest in paying zakat in BAZNAS DKI Jakarta during the pandemic Era. While partially the two variables, namely the digitalization variable and the zakat knowledge variable, both have a positive and significant effect on the interest in paying zakat in BAZNAS DKI Jakarta during the pandemic Era. Although in the pandemic era, the interest in paying zakat remains good and concern for fellow Muslims in the Ciracas area has received a positive response. So our hope is that the DKI Jakarta BAZNAS institution can increase the socialization of digitalization and zakat knowledge to the community.